Synthesis and biological evaluation of aurones as potential neuroprotective agents: structure-activity and mode of action studies. - Lee , Chong Yew
A series of aurone derivatives carrying amine and carbamate functionalities at various positions of the scaffold was designed and synthesized with the premise of developing a reasonably small sized multitargeting compound for neuroprotection while maintaining good drug-like properties.